A cryogenic silicon interferometer for gravitational-wave detection. (28th July 2020) - Adhikari, R X; Arai, K; Brooks, A F; Wipf, C; Aguiar, O; Altin, P; Barr, B; Barsotti, L; Bassiri, R; Bell, A; Billingsley, G; Birney, R; et al.
Abstract: The detection of gravitational waves from compact binary mergers by LIGO has opened the era of gravitational wave astronomy, revealing a previously hidden side of the cosmos. To maximize the reach of the existing LIGO observatory facilities, we have designed a new instrument able to detect gravitational waves at distances 5 times further away than possible with Advanced LIGO, or at greater than 100 times the event rate. Observations with this new instrument will make possible dramatic steps toward understanding the physics of the nearby Universe, as well as observing the Universe out to cosmological distances by the detection of binary black hole coalescences. This article presents the instrument design and a quantitative analysis of the anticipated noise floor.